Computable General Equilibrium Modeling : Theory and Applications - Castellanos, Kenneth; Feltenstein, Andrew; Sedrakyan, Gohar (London ; New York : Routledge Taylor & Francis Group, 2024)
"Many books have been written on computable general equilibrium (CGE) modeling. However, there are certain important areas for economic policy that have been largely overlooked. This intermediate/advanced text presents the topic as a methodology for the analysis of macro and fiscal policies in modern economies, while introducing levels of disaggregation that are beyond the scope of standard macro models. The book begins by presenting the historical and intuitive background of general equilibrium analysis. Moving on, computer software is introduced to derive numerical solutions for economic models. The authors provide examples of code, bringing in data sources that have become the foundations of CGE applications. The methodology presented here, which differs from other CGE books, includes financial assets, government budget deficits, and debt financing of private investment. These topics are analysed in the context of dynamic optimization, generating endogenous variables such as inflation, interest, and growth rates. The book also devotes significant attention to the applications of CGE models to developing economies. This textbook comes with a range of downloadable supplements and will be a valuable resource for students taking a CGE course as part of a programme in advanced microeconomics, macroeconomics, development economics, or international trade economics"--
Includes bibliographical references and index.
Keywords: Computable General Equilibrium Models